Depression and the use of conversational AI for companionship among college students: the mediating role of loneliness and the moderating effects of gender and mind perception - Lai, Lizu; Pan, Yiyu; Xu, Ranyuan; Jiang, Yanglang (Frontiers in Public Health, 2025)
IntroductionThe present study aimed to examine the relationship between depression and the use of conversational AI for companionship (UCAI-C) among college students. It further sought to investigate the mediating role of loneliness and the moderating roles of gender and mind perception in this association.MethodsA cross-sectional survey was conducted with 1,379 college students (Mean age = 21.93 years; 616 females, 763 males) using four validated instruments. Structural equation modeling was employed for data analysis.ResultsDepression was found to be positively associated with UCAI-C. This relationship was significantly mediated by loneliness. Moreover, both gender and mind perception moderated the pathways between depression, loneliness, and UCAI-C.ConclusionThe findings illustrate how individuals’ mental states can influence their use of companion AI. They highlight significant individual differences (gender and mind perception) in these relationships, contributing to the theoretical understanding of factors governing human interaction with AI chatbots.